HOW READY ‘INDONESIAN ENGLISH’ IS TO LAUNCH: AN EMIC PERSPECTIVE - Hanafi, Hanafi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
This is a qualitative study investigating the strength of the proposition of Indonesian English (Indolish) as a potentially emerging English variety from the outer/expanding circle from an emic perspective. This proposed variety does not yet exist even as a de facto English variety spoken in Indonesia or elsewhere. Nonetheless, the growing spread of English used by Indonesians has frequently prompted the idea of promoting the establishment of Indolish as a new English variety in the World Englishes areas for Indonesians. To clarify this early signal, an exploratory study was conducted to investigate the perspective of Indonesian postgraduate students who pursued their higher degrees in some Australian universities and whose overseas learning and language contact experience should bring them into a direct contact with a wide range of English varieties and thereby allowing them to better reflect on the significance of creating a special type of English for Indonesians. Seven participants responded to the three open-questioned survey questionnaire sent to two mailing list groups of Indonesian Postgraduate students. Two participants prefer to have Indolish while five others disagree with the idea. Majority of the participants show a strong nationalistic identity indicating a stagnant foundation process in Schneider’s Dynamic Model  in Indonesian context. Nevertheless, the participants demonstrate a strong dependence on English NS norms which confirm Kachru’s proposition and indicate their rejection of Norton’s notion of ownership of English language. In conclusion, these participants view that Indonesian English does not seem ready to launch yet.